2006
DOI: 10.1177/1049732306287599
|View full text |Cite
|
Sign up to set email alerts
|

Internet Recruitment and E-Mail Interviews in Qualitative Studies

Abstract: In 2004, 111 million adults accessed the Internet looking for health and medical information. Qualitative researchers can apply long-standing principles of recruitment and interviewing to the Internet. The purpose of this article is to examine the theoretical and methodological aspects of Internet recruitment and e-mail interviewing. The authors address issues of appropriateness, adequacy, representativeness, sample bias, data fraud, flexibility and consistency in interviewing, timing, elimination of the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
143
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 26 publications
(57 reference statements)
1
143
0
2
Order By: Relevance
“…Hamilton and Bowers (2006) suggest that researchers should 'select the most appropriate Internet site to place an announcement of the study ' (p. 825). Two profiles with the username 'TinderStudy' were created: One male and one female, both with a reported age of 25 years.…”
Section: Methodsmentioning
confidence: 99%
“…Hamilton and Bowers (2006) suggest that researchers should 'select the most appropriate Internet site to place an announcement of the study ' (p. 825). Two profiles with the username 'TinderStudy' were created: One male and one female, both with a reported age of 25 years.…”
Section: Methodsmentioning
confidence: 99%
“…However, recently email interviews have been introduced as an appropriate alternative, as outlined by Hamilton and Bowers (2006). Therefore, interviews of participants in the initial study were performed either over the phone or by email, depending on the participants' preferences.…”
Section: Interviews With Research Participantsmentioning
confidence: 99%
“…Structured interview is used in e-mail interview. Hamilton and Bowers [40] recommend initiating the process with three or four questions of a general nature and then following that with four or five cycles of three to four questions, when researches use e-mail interview. The researchers have time between receiving answers and sending the next set of questions to reflect on how best to follow up on the information received.…”
Section: E-mail Interviewmentioning
confidence: 99%
“…Any researcher could contact any interviewee as long as they have an online access. Second, it can eliminate transcription reliability because e-mail is a written data collection [40]. In face to face interview, the transcription of interview is an important issue because there may be some mistakes in the process of transcribing the interview.…”
Section: E-mail Interviewmentioning
confidence: 99%
See 1 more Smart Citation